Senecio rodolfoi (Asteraceae: Senecioneae), a replacement name for S. luridus Phil. from Chile - Wu, Xing; Shao, Yun-Yun; Guo, Xin-Qiang; Liu, Li-Hui (Phytotaxa, 2020)
Senecio rodolfoi (Asteraceae: Senecioneae) is proposed here to replace S. luridus Phil., which is a later homonym of S. luridus Salisb. and thus illegitimate.